Analisis Ketepatan Frekuensi Pembangkit Clock Berbasis Mikrokontroler - Freedy Kurniawan (Faculty of Industrial Technology Universitas Islam Indonesia, 2008)
Many electronics experience require clock generator. In common, analog clock generator able to generate clock signal with 5% error, and digital clock generator can generate with 0.1% error. Microcontroller-based clock signal generator has crystal accuracy. The useful frequency range that can be generated is between 1 Hz and 1 MHz when the microcontroller operating at a 24 MHz clock frequency. A 1 MHz frequency output can be generated by execute continuously a one-cycle-instruction to complement the pin output. To generate a specific frequency below 1 MHz, the other instruction(s) such as nooperation can be inserted to delay the next instruction. Kata kunci: pembangkit clock, mikrokontroler, galat.